Where No One Should Live : A Novel - Miller, Sandra Cavallo (Book collections on Project MUSE., 2021)
"Public health physician Dr. Maya Summer faces a myriad of medical challenges as she comes to grips with her uneasy past. Helped by faculty physician Alex Reddish, who withstands his own identity trials, she uncovers the grave truth behind a series of illnesses as she and Reddish draw close to one another"--